The Association of Art with Technology as the Basis of the Russian Constructivsm Aesthetic and Ideological Targeting Application - Tsoumas, Johannis (2013)
This paper aims at documenting the non-negotiable relationship between art and technology, two important cultural issues whose union has deep roots in the history of mankind. Based on this principle, the author takes an interest in a case of visual/mechanical/functional innovation in art history, philosophy and work of Russian constructivists, a newly jumble of values, which also enhanced concepts opposing the advancement, such as those of utopia and propaganda, which eventually helped document the identity of art with life itself. The positions of the author show that this significant relationship was the basis which great movements of modern art in the beginning, the middle and the end of the 20th century relied upon, many of which were deeply affected by the phenomenal technological developments of the time.